# day 10 - implicit differentiation - 10 - implicit آ  differentiation implicit differentiation  Post on 17-Jun-2020

3 views

Category:

## Documents

1 download

Embed Size (px)

TRANSCRIPT

• #BEEBETTER at www.tutorbee.tv

Differentiation Implicit Differentiation

Level 8

12

IMPLICIT DIFFERENTIATION The equation of an explicit function has its dependent variable on one side of the equal sign and the independent variable(s) on the other side:

𝑦 = 𝑥\$ + 2𝑥 − 1

In the equation of an implicit function dependent variable is not alone:

2𝑥\$𝑦 − 𝑥 𝑦 = 2𝑥

Recall that the derivative of the 𝑦 is 𝑦′ or 𝑑𝑦/𝑑𝑥. Particularly in the last notation, we refer to the derivative as “the derivative of 𝑦 with respect to 𝑥.” When taking the derivative of an implicit function, whenever you take the derivative of 𝑦, you must multiply by 𝑑𝑦/𝑑𝑥 or 𝑦′ (by Chain Rule). So, the derivative of 𝑥\$ with respect to 𝑥 is:

𝑥\$ . = 2𝑥 ∙ 𝑑𝑥 𝑑𝑥

= 2𝑥

But the derivative to 𝑦\$ with respect to 𝑥 is:

(𝑦\$)′ = 2𝑦 ∙ 𝑑𝑦 𝑑𝑥

After taking the derivative of both sides, isolate for 𝑑𝑦/𝑑𝑥 to get the derivative. This process is called implicit differentiation. EXAMPLE: Find the derivative of the circle: 𝑥\$ + 𝑦\$ = 25. SOLUTION: We’ll take the derivatives of both sides and isolate for 𝑑𝑦/𝑑𝑥:

2𝑥 + 2𝑦 ∙ 𝑑𝑦 𝑑𝑥

= 0

2𝑦 ∙ 𝑑𝑦 𝑑𝑥

= −2𝑥

𝑑𝑦/𝑑𝑥 = −𝑥/𝑦

EXAMPLE: Find the derivative of 𝑥𝑦 + 𝑦 = 2𝑥 − 1. SOLUTION: Notice that the first term is a product of two functions: 𝑥 and 𝑦. We’ll need to use product rule to differentiate:

1 𝑦 + 𝑥 ∙ 𝑦′ + 𝑦′ = 2 + 0

• #BEEBETTER at www.tutorbee.tv

Differentiation Implicit Differentiation

Level 8

13

Move 𝑦 to the right side and factor out the 𝑦′:

𝑦′ 𝑥 + 1 = 2 − 𝑦

Now isolate for 𝑦′:

𝑦′ = − 𝑦 − 2 𝑥 + 1

EXAMPLE: Find the derivative of 𝑥𝑦 = 4 both implicity and explicitly. SOLUTION: We can solve for 𝑦 to obtain an explicit equation:

𝑦 = 4 𝑥 = 4𝑥56

Then take the derivative:

𝑦. = −4𝑥5\$ = − 4 𝑥\$

Implicitly, we could use product rule:

1 𝑦 + 𝑦. 𝑥 = 0 𝑥𝑦. = −𝑦 𝑦. = −𝑦/𝑥

This may look different but recall that 𝑦 = 4/𝑥. We can subsitute that explicit equation into the derivative and see that it is the same expression:

𝑦. = −4 𝑥 𝑥

= − 4 𝑥\$

Manipulating Functions You can manipulate functions before taking the derivative in order to avoid quotient rule and get rid of square roots. For example:

𝑦 − 1 𝑥

= 𝑥𝑦 3

Square both sides to obtain:

𝑦\$ − 2𝑦 + 1 𝑥\$

= 𝑥𝑦 9

Then cross multiply:

9𝑦\$ − 18𝑦 + 9 = 𝑥:𝑦

This is an easier function to differentiate.

Recommended